2022
DOI: 10.3390/cells11142148
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Upregulation of Transcription Factor TFDP1 Binding Promoter Activity Due to RBP4 g.36491960G>C Mutation on the Proliferation of Goat Granulosa Cells

Abstract: Retinol-binding protein 4 (RBP4), a member of the lipocalin family, is a specific carrier of retinol (vitamin A) in the blood. Numerous studies have shown that RBP4 plays an important role in mammalian embryonic development and that mutations in RBP4 can be used for the marker-assisted selection of animal reproductive traits. However, there are few studies on the regulation of reproduction and high-prolificacy traits by RBP4 in goats. In this study, the 5′ flanking sequence of RBP4 was amplified, and a G>C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…According to recent reports, PTRH2 mutations have been shown to be one of the molecular mechanisms leading to ataxia and cerebellar atrophy in patients with multisystem neurological, endocrine and pancreatic diseases in infancy ( Picker-Minh et al, 2022 ). The TFDP1 gene controls both the transcriptional activity of cellular genes and was also involved in the cyclic regulation of cellular genes, affecting cell proliferation and apoptosis ( Hitchens and Robbins, 2003 ; Liu et al, 2022 ). Previous studies have found that the E2F-related transcription factor TFDP1 may be involved in the induction of genes related to functional modules in the transcriptome of ischemic neurons ( Jin et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reports, PTRH2 mutations have been shown to be one of the molecular mechanisms leading to ataxia and cerebellar atrophy in patients with multisystem neurological, endocrine and pancreatic diseases in infancy ( Picker-Minh et al, 2022 ). The TFDP1 gene controls both the transcriptional activity of cellular genes and was also involved in the cyclic regulation of cellular genes, affecting cell proliferation and apoptosis ( Hitchens and Robbins, 2003 ; Liu et al, 2022 ). Previous studies have found that the E2F-related transcription factor TFDP1 may be involved in the induction of genes related to functional modules in the transcriptome of ischemic neurons ( Jin et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%